The impact of somatic symptoms on depressive and anxiety symptoms among university students in central Serbia - Simic Vukomanovic, Ivana; Mihajlovic, Goran; Milovanovic, Dragan; Kocic, Sanja; Radevic, Svetlana; Djukic, Svetlana; Vukomanovic, Vladimir; Djukic Dejanovic, Slavica (Vojnosanitetski pregled, 2020)
Background/Aim. Depression and anxiety problems are a major public health concern due to their high prevalence rates, difficult treatment, and often chronic course. This study examined the impact of somatic symptoms on depressive and anxiety symptoms among university students in Serbia. Methods. A cross-sectional study was performed among 1,940 students using a questionnaire specially designed for this study which included presence of Somatic and Non-specific Mental Symptoms (SNMS), Beck Depression Inventory and Beck Anxiety Inventory. The presence of somatic and associated non-specific mental symptoms over the last six months served as the basis for creating a new variable called SNMS score. Results. Receiver operating characteristic (ROC) curve showed that the SNMS score might be a very good marker for the distinction of students with or without depressive symptoms (area = 0.754, p < 0.05). The threshold value was 8.50 (sensitivity 67.6%, specificity 69.4%). Binary logistic regression showed that Odds ratio was 1.052 [95% confidence interval (CI) 1.045–1.059], which means that an increase in the value of the SNMS score by 1 increases the risk of depressive symptoms by 5.2%. ROC curve showed that the SNMS score might be an excellent marker for the distinction of students with or without anxiety symptoms (area = 0.800, p < 0.05). Limit value (cut-off) was 7.50 (sensitivity 74.2%, specificity 71.6%). Binary logistic regression showed that odds ratio was 1.056 (95% CI 1.049–1.064), which means that increasing the value of SNMS score by 1 increases the risk of anxiety symptoms by 5.6%. Conclusion. The SNMS score might be a state marker for the screening and distinction of students with depressive symptoms, and excellent state marker for screening and making distinction between students with anxiety symptoms and the students who do not have these symptoms.